Welding skills (sách photo) - Moniz B. J (American technical publishers, 2004)
The third edition begin with an intruduction to the welding process and welding in industry. Thruogh the text an emphasis is placed on fundamental principles of welding processes, eequipment, welder performence qualification, anf weld evaluation and testing. The text also covers the lastest technology in welding metallurgy, metal weldability, distortion control, robotics, and material standards.